2018
DOI: 10.1007/s00239-018-9851-y
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Duplication of Drosophila Cid and Cenp-C Genes Resulted in Accelerated Evolution and Male Germline-Biased Expression of the New Copies

Abstract: Despite their essential role in the process of chromosome segregation in eukaryotes, kinetochore proteins are highly diverse across species, being lost, duplicated, created, or diversified during evolution. Based on comparative genomics, the duplication of the inner kinetochore proteins CenH3 and Cenp-C, which are interdependent in their roles of establishing centromere identity and function, can be said to be rare in animals. Surprisingly, the Drosophila CenH3 homolog Cid underwent four independent duplicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…2018 ). Interestingly, the cenp-c gene was also found to have duplicated during evolution, something that was probably expected, given its association with Cal1 and dCENP-A ( Rosin and Mellone 2016 ; Teixeira et al . 2018 ).…”
Section: Drosophila As a Model Organism To Understand Neocen...mentioning
confidence: 92%
See 2 more Smart Citations
“…2018 ). Interestingly, the cenp-c gene was also found to have duplicated during evolution, something that was probably expected, given its association with Cal1 and dCENP-A ( Rosin and Mellone 2016 ; Teixeira et al . 2018 ).…”
Section: Drosophila As a Model Organism To Understand Neocen...mentioning
confidence: 92%
“…2012 ; Rosin and Mellone 2016 ; Kursel and Malik 2017 ). While, in melanogaster , dCENP-A is encoded by a single copy gene, two recent studies have reported that in other species, there have been five independent duplications of the genes during evolution, with the products retaining their centromeric localization but seems that their functions might be nonredundant, while some are expressed primarily in the male germline ( Kursel and Malik 2017 ; Teixeira et al . 2018 ).…”
Section: Drosophila As a Model Organism To Understand Neocen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Species from the Sophophora subgenus typically express three of them (Cid1, Cid3, and Cid4), whereas the Drosophila subgenus expresses two paralogs (Cid1 and Cid5). More recently, a novel Cid duplication was described for the Drosophila subgenus (Cid6) [56]. All the variants tested in D. auraria show centromeric localization, suggesting that all retained centromeric function [51].…”
Section: Cenp-a Adaptations For Meiosismentioning
confidence: 98%
“…After the duplication, one of the genes can assume more specialized functions, whereas the other one still performs its initial role. Interestingly, CENP-A duplicates differ mostly in the N-terminal tail sequence [51][52][53][54][55][56].…”
Section: Cenp-a Adaptations For Meiosismentioning
confidence: 99%